Urethral striated muscle and extracellular matrix morphological characteristics among mildly diabetic pregnant rats: translational approach - Piculo, Fernanda [UNESP]; Marini, Gabriela [UNESP]; Pascon Barbosa, Angelica Mercia [UNESP]; Damasceno, Débora Cristina [UNESP]; Matheus, Selma Maria Michelin [UNESP]; Felisbino, Sergio Luis [UNESP]; Daneshgari, Firouz; Rudge, Marilza Vieira Cunha [UNESP] (Springer, 2014)
Diabetes mellitus (DM) during pregnancy is associated with high levels of urinary incontinence (UI) and pelvic floor muscle dysfunction. Mild DM can lead to changes in urethral striated muscle and extracellular matrix (ECM) in pregnant rats considering both structures as an entire system responsible for urinary continence.Ninety-two female Wistar rats were distributed in four experimental groups: virgin, pregnant, diabetic, and diabetic pregnant. In adult life, parental nondiabetic female rats were mated with nondiabetic male rats to obtain newborns. At the first day of birth, newborns received citrate buffer (nondiabetic group) or streptozotocin 100 mg/kg body weight, subcutaneous route (mild DM group). At day 21 of the pregnancy, the rats were lethally anesthetized and the urethra and vagina were extracted as a unit. Urethral and vaginal sections were cut and analyzed by: (a) cytochemical staining for ECM and muscle structural components, (b) immunohistochemistry to identify fast- and slow-muscle fibers, and (c) transmission electron microscopy for ultrastructural analysis of urethral striated muscle.In comparison with the three control groups, variations in the urethral striated muscle and ECM from diabetic pregnant rats were observed including thinning, atrophy, fibrosis, increased area of blood vessels, mitochondria accumulation, increased lipid droplets, glycogen granules associated with colocalization of fast and slow fibers, and a steady decrease in the proportion of fast to slow fibers.Mild DM and pregnancy can lead to a time-dependent disorder and tissue remodeling in which the urethral striated muscle and ECM has a fundamental function.
Keywords: Diabetes; Extracellular matrix; Pregnancy; Rats; Urethral striated muscle